Aesthetics in hardscape design: a study of perception, preference, and application in Bosco Plaza - Updike, Miles Douglas (Kansas State University, 2020)
Hardscape design is an essential aspect of public space, especially for urban plazas, which typically consist of paved open areas for circulation, gathering, and sitting. A successful public space relies on multiple factors including aesthetics. Yet with near limitless possibilities for hardscape design, little is known on what aesthetic attributes people prefer, and if the aesthetics of hardscape influence perceptions of attractiveness, safety, welcoming, comfort, and interest in a public space. This project aims to generate knowledge about aesthetic preferences for select attributes of hardscape design, specifically color, pattern, frame, edge, and size, and how hardscape designs may influence perceptions of public space. To accomplish this goal, Bosco Plaza, a large public space on the campus of Kansas State University, was selected as the study site. The research consists of three main components. First, a preference survey was issued to students and faculty in the College of Architecture, Planning, and Design at K-State, to assess what aesthetic attributes of hardscape designs were most preferred, using Likert-scale questions. The survey findings, along with results from a site analysis, helped inform a comprehensive redesign of Bosco Plaza, which included six alternative concepts for its hardscape design. The hardscape design concepts were modeled and rendered digitally to create images for the second survey, where participants were asked to express their perceptions of attractiveness, safety, welcoming, comfort, and interest for each. Overall findings reveal that while successful hardscape designs rely upon many factors, hardscape designs which implement a diversity of colors and a randomness of patterns are most aesthetically preferred. Additionally, it was found that more attractive hardscapes also positively impact perceptions of safety, welcoming, comfort, and interest in public space.
Keywords: Hardscape; Paving; Design; Aaesthetics; Bosco Plaza; Public space; Preference; Perception; Application